CBMT-23. MODULATION OF HYPERSYNAPTIC MICROENVIRONMENT DIFFERENTIALLY PROMOTES GLIOMAGENESIS ACROSS PIK3CA VARIANTS. (5th November 2018) - Yu, Kwanha; Hatcher, Asante; Woo, Jungsung; John Lin, Chia-Ching; Kong, Kathleen; Mohila, Carrie; Lozzi, Brittney; Creighton, Chad; Noebels, Jeffrey; Deneen, Benjamin
Abstract: Genetic mutations remain one of the principle drivers for glioblastoma multiforme, a devastating disease with the poorest prognosis; however, much like other cancers mutations are both a cause and consequence of glioma. While there is a wealth of patient genomics data, they do not properly discern or address whether annotated genetic perturbations are causative "driver" events or consequential "passenger" mutations. To address this, we developed a screening platform where we can screen up to 50 different genetic factors, in vivo. In combination with next generation sequencing, we identified the most potent candidate drivers. Additionally, we've comparatively analyzed 30 different alleles of PIK3CA in vitro. Using these approaches, we identified candidate drivers and individually validated these alleles. Testing 7 variants in vivo, we identified C420R and M1043I as rare and previously uncharacterized driver mutations in GBM. Additionally, we identified variants that do not promote tumor growth, demonstrating that each variant differentially drives gliomagenesis. Subsequent molecular profiling of driver variants suggested differential synaptic environments which correlated with seizure activity. We further characterized this synaptic deregulation, revealing that individual variants can differentially modulate the hypersynaptic microenvironment, independent of tumor context. Taken together with recent work revealing that local synaptic activity can promote tumor growth, this would suggest that specific variants of PIK3CA differentially drive gliomagenesis by differentially modulating the hypersynaptic profile of the tumor microenvironment. In sum, our study reveals: 1) a novel screening approach whereby we can screen 50 different factors in vivo, 2) novel GBM-relevant driver alleles C420R and M1043I previously not characterized in vivo, 3) that even single amino acid alterations across driver mutations can drastically alter gliomagenic programs, and 4) one differential mechanism by which PIK3CA variants differentially promote gliomagenesis is by deregulating synaptic microenvironment.